The level of development of housing - municipal services - one of the main indicators of development of the region . - Корганбаева, А. Б . (Journal of Economic Research & Business Administration, 2015)
In today's society is a topical issue of housingcommunal services (HCS ) . The reason for this is the fact that this area is closely related to people's welfare provision as a separate city and the country as a whole. Improving Housing is one of the main directions of state policy activities.